The Epilepsy Book: A Companion for Patients : Optimizing Diagnosis and Treatment - Valeta, Thalia (Springer International Publishing : Imprint: Springer, 2017)
This book presents scientific evidence about epilepsy along with straightforward guidance and recommendations. Responses to frequently asked questions and clarification of uncertainties are provided to empower patients to optimize their medical, psychological and social care. This book helps mediate between patients and health care professionals and can assist both sides to understand the condition of epilepsy at all levels. The information provided in the book empowers patients to share decision making with their carers and clinicians and enables them to make informed decisions, by taking into account the best scientific evidence, as well as the patients' values and preferences. The Epilepsy Book: A Companion for Patients is ideal for patients with epilepsy and their carers, and will also be of interest to health care professionals, medical students and teachers. Thalia Valeta's approach to epilepsy facilitates deeper understanding of the unmet needs and expectations of patients.
Keywords: Popular works.; Neurology.; Medicine.; Health.; elektronické knihy; electronic books